Effect of Dietary Linseed on Egg Quality of Laying Quail - Al-Daraji, Hazim J.; Razuki, W.M.; Al-Hayani, W.K.; Al-Hassani, A.S. (International Journal of Poultry Science, 2010)
This experiment was performed to investigate the effect of dietary supplementation with linseed on egg quality of laying quail. A total of 320 Japanese quail (Coturnix coturnix japonica) 9-wk old were allocated to 4 treatment groups with 4 replicates containing 20 quail each. Birds were fed commercial diet containing 0% (C), 2% (T1), 4% (T2) or 6% (T3) linseed. Birds received water and diet ad libitum during the total period of experiment. Egg quality characteristics were monitored over 3 consecutive 21-d periods. Egg quality criteria involved in this experiment were egg weight, yolk diameter, yolk height, yolk weight, albumen height, albumen weight, shell weight, shell thickness, Haugh unit, albumen percentage, yolk percentage and shell percentage. Results revealed that supplementing diet of laying quail with linseed resulted in significant increase in total means of egg weight, yolk diameter, albumen height, shell thickness, Haugh unit, albumen percentage and albumen weight. Total means of shell weight and yolk percentage were not significantly (p>0.05) different from quails consuming 0, 2, 4 or 6% linseed; However, total mean of shell percentage was reduced (p<0.05) in laying quails fed linseed when compared to control group. In conclusion, Feeding laying quails with different levels of linseed (2%, 4%, or 6%) caused significant improvement as regards most of egg quality parameters included in this experiment. Therefore, adding linseed to the ration could be used as a good tool for improving productive performance of Japanese quail.